PREPARING STUDENT TEACHERS THROUGH PHYSICAL EDUCATION TEACHING AND LEARNING: A STUDY IN ONE RURAL UNIVERSITY OF THE EASTERN CAPE PROVINCE - Ntando Elliot Mpahla; Bulelwa Makena (International Journal of Innovative Technologies in Social Science, 2023)
The findings from this study indicated that the programmes of student teacher education are not implemented in totality as there is no module for Physical Education (PE) in the programmes of study in the Faculty of Education. This study aimed at investigating the preparation of student teachers through PE teaching and learning in one rural university of the Eastern Cape Province. PE teaching and learning for student teachers at a higher education institution means preparing future teachers in totality to acquire vibrant and active public schools. This study used a qualitative research methodology where data was collected from fifteen (15) participants composing of five (05) B Ed Foundation Phase Teaching student teachers, five (05) Postgraduate (PGCE) student teachers and five (05) lecturers from the Faculty of Education. Semi-structured interviews were used as instruments of data collection. Participants for the study were selected through purposive sampling because of their defining characteristics about the knowledge of the problem under study. The study concludes that it is awkward to train and develop student teachers for public schools without the knowledge of PE teaching and learning. There is a recommendation to infuse training of student teachers in PE, henceforth, as novice teachers get employment at schools, they are allocated among other duties, extra-mural activities such sport.